História da ciência nos livros didáticos de física - (:unkn) unknown (Universidade Federal do Pampa, 2014)
This study aims to investigate two collections of textbooks of Physics selected in PNLD 2012-2014 and that are used in the Romaguera Correa and Marechal Candido Rondon high schools in the Uruguaiana/RS. This analysis seeks to understand the conditions and quality of the historical information presented in textbooks. Based on the analysis we found that in general the history of science is presented with focus in the characters and dates without considering the social context and the evolution of science. However the textbooks present some good examples of historical contextualization, demonstrating that it is possible through an effort of authors to present in the textbooks the physics as a science in constant progress contributing to the society development.
Keywords: Ensino médio; Física; História da Ciência; High school; Science History; Physical; CNPQ::CIENCIAS HUMANAS